Abrasive waterjet cutting technology - Chua, Albert Kee Sew. (2009)
This project is primarily aimed to study some essential process parameters for Abrasive Waterjet Cutting (AWJ) Process. It has been performed in two phases. The first phase concentrates on the identification of setting levels of the specified parameters. During which, specimen of stainless steel, SS304 were cut by the abrasive waterjet and the kerf surface quality was measured. Techniques associated with Design of Engineering Experiments such as Taguchi and Analysis of variance (ANOVA) were used for the analysis.